Barriers and enablers to implementing mental well‐being programs through Australian rural football clubs—A qualitative descriptive study. (17th May 2020) - Hutchesson, Heidi; Dollman, James; Baker, Amy; Kernot, Jocelyn
Abstract: Issue addressed: Suicide rates in rural Australia are almost twice as high as those in urban areas. In rural communities, football clubs are often the 'hub' of the community and are being explored as an avenue to deliver mental health and well‐being promotion. The aim of this study was to explore barriers and enablers for programs promoting mental health and well‐being through rural Australian football clubs. Method: This qualitative descriptive study included 12 individuals of 10 rural clubs affiliated with the South Australian National Football League. Recruitment occurred via emails to club secretaries/presidents. Semi‐structured telephone interviews explored mental health and well‐being issues experienced in clubs, previous involvement with mental well‐being programs and potential barriers/enablers for future programs. Interviews were transcribed verbatim and analysed thematically. Results: Thematic analysis identified three themes encompassing barriers and enablers: (1) more than a football club, (2) attitudes towards mental health and (3) what is needed to implement a program. The third theme had subthemes of resources, importance of timing, mental health initiatives and components of a program. Conclusion: Key barriers included difficulty getting people involved due to individual attitudes towards mental health, and not having the finances/resources to implement a program. Major enablers included the important role the football club serves in the community, the inclusion of speakers with credibility and making the program engaging. So what?: This study identifies key factors which may impact on community engagement and program effectiveness for mental health and well‐being programs delivered via rural football clubs.